2013
DOI: 10.1111/j.1475-5890.2013.12011.x
|View full text |Cite
|
Sign up to set email alerts
|

Gender, Time Use, and Children's and Adolescents' Well‐Being: Implications for Public Policies*

Abstract: This paper has two main goals. The first is to analyse and measure gender differences in children's and adolescents' well-being by using a capability approach. The second aim is to identify the parameters that can help design policies to improve children's and adolescents' well-being. The econometric model used is a multiple indicator multiple causes (MIMIC) model, belonging to the class of structural equation models. The estimation is done on a sample of 10-to 17-year-old girls and boys and uses micro-data fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Children can also influence the duration and sequence of parents’ activities because young children must have care throughout the day and older children require coordination and supervision (Kingston and Nock 1987). Research has supported this as parents have been found to adjust schedules in order to care for children (Hamermesh 2000; Klaveren and Brink 2007; Presser 1987, 1994), even if in gendered ways (Galvez-Muñoz et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Children can also influence the duration and sequence of parents’ activities because young children must have care throughout the day and older children require coordination and supervision (Kingston and Nock 1987). Research has supported this as parents have been found to adjust schedules in order to care for children (Hamermesh 2000; Klaveren and Brink 2007; Presser 1987, 1994), even if in gendered ways (Galvez-Muñoz et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, through their role in the construction of future conversion factors, they may or may not take on their social responsibility in doing care work as pointed out by the social provision approach. On the other hand, it is important to include the notion of evolving capabilities (which incorporates the concept of agency) and to highlight that some capabilities are also instrumental and foster the development of other capabilities both during childhood and adult life, education being a clear example (Gálvez –Muñoz et al, 2013; Biggeri and Karkara, 2014; Comim et al, 2011).…”
Section: Children and The Capabilities Approach: A Dialoguementioning
confidence: 99%
“…According to supporters of this second option, it is possible to select a series of capabilities as specific theoretical or empirical objectives. In fact, the literature shows that the capabilities proposed for analyzing children’s well-being vary depending on the context and the object of the research (Addabbo et al, 2004, 2014; Anich et al, 2011; Ben-Arieh, 2008; Biggeri et al, 2006; Di Tommaso, 2007; Gálvez–Muñoz et al, 2013).…”
Section: Children and The Capabilities Approach: A Dialoguementioning
confidence: 99%
See 2 more Smart Citations